THE INFLUENCE OF WATER MIGRATION OF MICROELEMENTS ON THE ECOLOGICAL SOIL CONDITION OF UKRAINE - Moklyachuk, Lidiya; Furdychko, Orest; Yegorova, Tetiana (Emirates Journal of Food and Agriculture, 2015)
It is shown the role of natural geochemical processes of migration of trace elements for forming of food chains. Calculations of the coefficients of water migration Co, Zn, Mo, Mn, Cu and ionic strength of waters of small rivers in Ukraine were made. Intensity of water migration of chemical elements were assessed by coefficient (Kx), complex mobility of certain groups of chemical elements in aqueous solutions was evaluated by the coefficient of ionic strength of solutions (CIS). It is shown that spatial imbalance of quantity of microelements Zn, Mo, Co, Mn, Cu in soils Ukraine related with water mobility of these elements and the degree of metamorphization of natural waters.